Rethinking global political economy : emerging issues, unfolding odysseys - Tétreault, Mary Ann, 1942- (Routledge, 2003)
Innovative approaches to the fundamental issues of the global political economy, in particular post Cold War development, analyses of capital and negative aspects of globalization.
Keywords: International economic relations.; Globalization -- Economic aspects.; Globalization -- Social aspects.; Globalization -- Political aspects.; Mondialisation.; Mondialisation -- Aspect social.; Mondialisation -- Aspect politique.; globalism.; BUSINESS & ECONOMICS -- International -- General.; BUSINESS & ECONOMICS -- International -- Economics.; Globalization -- Economic aspects; Globalization -- Political aspects; Globalization -- Social aspects; International economic relations